Pengaruh Rebranding, Kualitas Layanan dan Brand Ambassador terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Sebagai Variabel Mediasi: Studi Kasus Pada Generasi Milenial dan Zilenial yang Menggunakan Gofood di Kota dan Kabupaten Mojokerto - Puspita Anggraini, Dita; Rahayu, Rahayu; Hidayat, M. Syamsul (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to determine the effect of rebranding, service quality, and brand ambassadors on GoFood consumer satisfaction and loyalty in Mojokerto with the population of Gen Z and Gen M. The sampling technique used is non- probability sampling with purposive sampling method and the number of respondents is 251 people. The results showed that rebranding had no effect on customer satisfaction, but service quality and brand ambassadors had a significant effect on customer satisfaction. In addition, rebranding and brand ambassadors have no effect on consumer loyalty, while service quality has a positive effect on consumer loyalty. Customer satisfaction also has a significant effect on customer loyalty. However, customer satisfaction does not mediate the relationship between rebranding and customer loyalty, but is able to mediate the effect of service quality and brand ambassadors on customer loyalty.